The Participation of Ageing Academicians in Private Universities in Malaysia - Murthy, Uma; Abdullah, Norehan; Abdullah, Hussin (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this study is to examine the participation of ageing academicians in private universities in Malaysia. The data collected using a quantitative method, particularly a stratified random sampling technique. A questioner was distributed among 200 ageing academician in SEGi University, Taylors University, Sunway University, Monash University, INTI University and Nilai University. The targeted population is ageing academician in the age of 55 to 60 years. The findings indicate that financial circumstances and health status influence the participation of ageing academician in private universities in Malaysia. Moreover, few recommendations are placed for overcome these challenges.